Using Rosetta Stone Software As Media In Teaching English Vocabulary (An Experimental Study At SDN No. 02 Lhoksukon) - Hanif, Hanif (STKIP Bina Bangsa Getsempena Banda Aceh, 2015)
Using of Rosetta Stone Software as media in teaching English vocabulary. The aim of this study is to examine the effectiveness of using Rosetta Stone Software in teaching vocabulary. The data were obtained from 64 students who belong to the two classes (groups), the control group and the experimental group, as the representative of all fifth grades of SDN No 02 Lhoksukon, Aceh Utara. The writer took two classes randomly for the sample of three parallel classes. The research instruments used to collect the data for this study were pre-test and post-test. The pre-test and the post-test were given to the two classes; the experimental class and the control class. The result of the test was studentsâ scores of the experimental group and the control group. This result was analyzed by using statistical formula in order to see if there is a significant difference between the students who were taught by direct method and the students taught by using Rosetta Stone Software as the media in teaching vocabulary. The use of Rosetta Stone Software focused on matching the pictures and meaning of some activities of Rosetta Stone Software shown on the screen. Base on explanation above, using Rosetta Stone Software as media also proves that the treatment has given some effects on studentsâ vocabulary improvement.Â Key Words: Rosetta Stone Software, Teaching vocabulary, Media